Otimização da produção de ácido 3-hidroxipropiônico por Escherichia coli via engenharia metabólica e de processos - Batista, Raquel Salgado (Universidade Federal de São Carlos, 2022)
The integration of substrates from bioprocesses is of great interest due to the need of destination for them and the possibility of converting them into value-added products. Among these substrates, the hydrolysates from biorefineries and glycerol obtained from the production of biofuels stand out. Listed as an important chemical platform that can be obtained from biomass by the U.S. Department of Energy, 3-hydroxypropionic acid (3-HP) becomes a product option to be obtained from the co-products mentioned above. The production of 3-HP by biological routes presents some advantages over chemical routes and has become increasingly feasible due to the continuous advancement in industrial biotechnology. To make this production feasible, bioprocesses have been developed from recombinant microorganisms. Thus, the application of genetic engineering in the modification of genes related to the metabolic pathway of these microorganisms allows the construction of strains capable of obtaining 3-HP from cheap substrates (e.g., glycerol, glucose, and xylose). A recombinant E. coli strain developed in our research group showed promising results through the β-alanine production route, but the insertion of the 3-HP production pathway in this strain resulted in a deficiency of cofactors, since the last reaction of the pathway is NADPH dependent. Therefore, the regeneration of this cofactor was evaluated by the expression of genes encoding the NADP+ dependent enzyme glyceraldehyde-3-phosphate dehydrogenase, so that the demand for this cofactor by the NADPH dependent pathways could be met. Overexpression of the gapN gene from Streptococcus equi zooepidemicus, which encodes an NADP+ dependent GAPDH, coupled with regulation of endogenous gapA transcription and the use of glycerol as a carbon source, resulted in 147% higher production compared to the control strain. The use of lactose as an induction agent for the lacUV5 promoter was also evaluated in this study and increased the final 3-HP concentration by about 7% compared to the production obtained by the same strain using 1mM IPTG as an induction agent. Furthermore, conditions with O2 restriction in the process showed that, for the pathway studied, 3-HP production is favored under aerobic condition, and oxygen restriction limits production and leads to acetate accumulation by the cell. Taken together, the strategies evaluated led to the second highest production of 3-HP by the β-alanine pathway reported so far in the literature.
Optimization of 3-hydroxypropionic acid production by Escherichia coli using metabolic and process engineering
Keywords: Ácido 3-hidroxipropiônico; β-alanina; Glicerol; Lactose; Fábrica celular; GPDH; 3-Hydroxypropionic acid; β-alanine; Glycerol; Cell factory; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA